HOMO IURIDICUS AND LEGAL REASONING - Dajović, Goran (Pravni zapisi, 2025)
The paper examines the method of ideal-typical concepts, which the author previously applied in his book Osnovi pravnog rasuđivanja (The fundamentals of legal reasoning). Since the book contains only a few remarks on the topic, the article aims to offer a systematic account of the method employed and its implications. In the book, the ideal type is constructed as homo iuridicus, the subject whose reasoning is guided exclusively by authoritative legal reasons. This subject is a rational, rather than an empirically existing agent. The paper argues that the ideal type provides a framework for conceptualizing legal reasoning without resort- ing to the idiosyncrasies of individual judges or particular legal communities. When the reasoning of such a homo iuridicus is compared to actual judicial practice, it becomes evident that judges do not always decide or justify their rulings solely by referencing authoritative legal reasons. In this way, the usefulness of Weber’s notion of ideal-typical concepts for jurisprudence is brought to light.